2022
DOI: 10.1007/978-3-031-09282-4_41
|View full text |Cite
|
Sign up to set email alerts
|

Informativeness in Twitter Textual Contents for Farmer-centric Plant Health Monitoring

Abstract: Data mining in social media has been widely applied in different domains for monitoring and measuring social phenomena, such as opinion analysis towards popular events, sentiment analysis of a population, detecting early side effects of drugs, and earthquake detection. Social media attracts people to share information in open environments. Facing the newly forming technical lock-ins and the loss of local knowledge in agriculture in the era of digital transformation, the urge to reestablish a farmer-centric pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This has been further heightened by the COVID-19 pandemic (Colussi et al , 2022). Farmers are participating in more farmer-to-farmer and farmer-to-rural professional conversations on Twitter (Jiang et al (2022). In their study of farmers’ adoption of no-till farming practices, Skaalsveen et al (2020) found that farmers favoured Twitter as a preferred means of SM communication as it enables easier peer interactions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has been further heightened by the COVID-19 pandemic (Colussi et al , 2022). Farmers are participating in more farmer-to-farmer and farmer-to-rural professional conversations on Twitter (Jiang et al (2022). In their study of farmers’ adoption of no-till farming practices, Skaalsveen et al (2020) found that farmers favoured Twitter as a preferred means of SM communication as it enables easier peer interactions.…”
Section: Literature Reviewmentioning
confidence: 99%